2003
DOI: 10.1007/s11661-003-0192-z
|View full text |Cite
|
Sign up to set email alerts
|

Density changes of iron during morphological healing evolution of internal fatigue microcracks

Abstract: Plastic-strain-controlled fatigue was performed on pure iron specimens with uniaxial symmetric tensioncompression loadings at room temperature. The as-fatigued specimens were then annealed in vacuum at 1173 K from 1 to 7 hours. The morphologies of internal fatigue microcracks were observed by scanning electron microscopy (SEM) in the as-fatigued and as-annealed specimens. The density of the specimens was measured with an electronic analytical balance. The density of the as-fatigued specimens decreased continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…The heat treatment method was also employed to restore the plasticity margin destroyed in cold plastic deformation and to avoid damage by Kolmogorov et al [13], and experimental data indicated that the micro-damages in metal materials heal. A series of researches on the internal crack healing in pure iron at high temperature were carried out by Zhang et al [14]. SEM observations showed that the micro-cracks changed to an unduloid-like shape at 2 h, then evolved into an array of circular voids at 5 h, with some isolated voids scarcely observed at 7 h. A series of experiments on crack healing in steel through the electric current pulse technique was carried out by Zhou et al [15], the cracks could partly heal through the electric current pulse at the solid state and the healing process was finished within a very short duration, and that the original microstructure in the area without crack did not change.…”
Section: Introductionmentioning
confidence: 99%
“…The heat treatment method was also employed to restore the plasticity margin destroyed in cold plastic deformation and to avoid damage by Kolmogorov et al [13], and experimental data indicated that the micro-damages in metal materials heal. A series of researches on the internal crack healing in pure iron at high temperature were carried out by Zhang et al [14]. SEM observations showed that the micro-cracks changed to an unduloid-like shape at 2 h, then evolved into an array of circular voids at 5 h, with some isolated voids scarcely observed at 7 h. A series of experiments on crack healing in steel through the electric current pulse technique was carried out by Zhou et al [15], the cracks could partly heal through the electric current pulse at the solid state and the healing process was finished within a very short duration, and that the original microstructure in the area without crack did not change.…”
Section: Introductionmentioning
confidence: 99%